L'ensenyament dels conceptes de força centrípeta i força centrífuga. Una proposta inspirada en la història mecànica - Casadellà Reig, Josep; Miró, C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
Textbook authors use many types of resources to teach centripetal acceleration, centripetal force and centrifugal force. They are resources between an intuitive and a formal perspective. We try to make a review, not exhaustive, of three points of view and also to present a new one supported on an original Newton’s idea, and which could present some advantages when teaching and learning these concepts.